Overview of viral hepatitis: a current study (Research, Society and Development, 2020)
Viral hepatitis (VH) is caused by five different types of viruses that have tropism in the liver tissue, with important differences between them and regional particularities. Thus, the present study aims to conduct a current bibliographic survey, disseminating information on epidemiological aspects, clinical manifestations, preventive forms, testing, and treatment of VH. This study is a bibliographic, qualitative review, with an exploratory characteristic, where searches were carried out in the virtual databases for articles, dissertations, theses, manuals, and epidemiological bulletins from 2010 to 2020. VHs are systemic infectious diseases, considered the main representatives of the “hepatocellular syndrome”. They can take an acute course or become chronic, with the acute phase being self-limited, with an average duration of 02 months, with a maximum period of up to 06 months; the chronic form is characterized by a period longer than 06 months with the virus in the body, causing repeated and incessant aggressions against hepatocytes. The pathology is oligosymptomatic until the patient develops characteristic symptoms such as ascites and hepatic encephalopathy; other ways of discovering that the individual has an HV are in blood tests during donations of blood components, prenatal tests, candidates for the hemodialysis program and in rapid testing campaigns. With this study, it was possible to outline the profile of the most vulnerable risk groups, making it possible to design prevention strategies, aiming to minimize the rate of contagion and epidemic episodes, reaching the global goal “NOHep” of WHO for the eradication of viral hepatitis as a problem public health by 2030.